Tinjauan Batas Usia Perkawinan Dalam Persfektif Psikologis dan Hukum Islam - Ongky Alexander (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2020)
Psychologically, Human Age Limits include, First, Childhood. Second, Adolescence, Third Adulthood, Fourth, Old Age. At the Adult Stage is calculated at the age of 21 years to about 40 years. Means that the age of marriage aged 19 years does not include the adult category. In general, marriage problems between men and women are not seen from the age factor but age limits affect the maturity of thinking and human development psychologically. Especially in the case of marriages that need to be considered is the age of maturity, since the enactment of Law No. 16 of 2019 concerning amendments to Law No. 1 of 1974 concerning marriages, the current marriage age limit between men and women is equal to the age of 19 years. Of course this becomes a problem, because at that age according to the psychological development of the ego is still relatively high. So the cause of early divorce at the age of about 25 years and over.